The shaman and the artist: a personal enquiry - Cull, Cleone (Rhodes University, Faculty of Humanities, Department of Fine Art, 1975)
This inquiry incorporates anthropological surveys on the life and character of the shaman, some writings of the American Plains Indians, and artist's, whose life and work reflects the power/life force so integral to the beliefs of these so called primitive cultures. Since the artist cannot be separated from his environment, the actions and reactions of society have also been explored. The method of inquiry has been to establish, first, the way of the shaman, and then the way of the artist. Although each artist, reflects only certain aspects of the enquiry, there is a strong affinity in the life and works of them all.
Keywords: Art, Shamanistic; Shamans; Artists